Vaccine communication strategies among healthcare workers as a reflection of the Israeli Ministry of Health’s communication strategies before and after the COVID-19 pandemic - Hijazi, Rana; Gesser-Edelsburg, Anat; Mesch, Gustavo S. (Frontiers in Public Health, 2024)
Background Healthcare workers play a central role in communicating information to the public regarding vaccines. Most of the literature has focused on healthcare workers' hesitancy and doubts about getting the flu vaccine themselves. However, few studies have dealt with how they perceive their role in communicating information regarding vaccines, especially following the COVID-19 pandemic. Objectives (1) To identify the communication strategies used by the Israeli Ministry of Health regarding vaccines during epidemic crises (before and after the COVID-19 pandemic); (2) To identify the communication strategies used by healthcare workers regarding vaccines before and after the COVID-19 pandemic. Methods A qualitative study based on in-depth interviews was conducted among healthcare workers and used a semi-structured protocol as a research tool. A total of 18 healthcare workers were sampled using purposeful and snowball sampling. Results Despite healthcare workers’ perception that there has been a decrease in trust in the Israeli Ministry of Health among the public following the COVID-19 outbreak, they still rely on the Israeli Ministry of Health as their primary source of information and use the same communication strategies (such as fear appeals and correcting information) as of the Israeli Ministry of Health to communicate with the public, healthcare providers, and other relevant stakeholders. Conclusion Healthcare workers have been shaped by the professional socialization processes within the health system, leading to a predominant reliance on established communication strategies and informational channels. This reliance underscores the importance of evolving these methods to better engage with the public. To address this, there is a compelling need to innovate and adopt new communication techniques that emphasize effective dialogue and transparent interactions. By doing so, healthcare professionals can ensure that their outreach is not only informative but also responsive to the diverse needs and preferences of the community.